INTEGRAL APPROACHES TO TEACHING SENIOUR SCHOOLCHILDREN AND THEIR IMPACT ON DEVELOPMENT OF A HEALTHY LIFESTYLE - Lyudmila N. Goncharova; Alexey P. Yurenev; Mourhaf Alnaser (National Research Mordova State University, 2016)
Introduction: the deterioration of health indicators among adolescents is an alarming tendency observed recently. The need for development of health-safeguarding behaviour in high school students of Saransk is obvious. The authors analysed the general health status of this group depending on implementation of various types of educational programmes in high schools. Materials and Methods: the data of arterial blood pressure, body mass index, food habits among high school students according to age, gender, nationality of schoolchildren and level of integration into educational programmes have been analysed. The research included 203 high school students from14 to 17 years old, 57 % boys and 43 % girls (grades 9 to 11) from two different schools of Saransk city with different educational programmes. Results: the research demonstrated a positive impact of sport programmes on health-preserving behaviour of high school students, resulted in stabilisation of arterial blood pressure, normal body mass and lower level of fast food consumption. Discussion and Conclusions: educational programmes focused on acceptance and implementation of healthy lifestyle could be considered as possible factors affecting health-preserving behaviour. The authors suggest paying more attention to these programmes' inclusion into educational process.